Massive Intraoperative Hypercarbia and Subcutaneous Emphysema in a Geriatric Patient with Cardiorespiratory Comorbidities Undergoing Laparoscopic Cholecystectomy: A Case Report - Steven Yoe (International Journal of Science and Society, 2026)
Laparoscopic cholecystectomy in geriatric patients imposes risk due to carbon dioxide (CO2), especially in patients with cardiovascular comorbidities. This report presents a 87 years old female with body mass index (BMI) of 17.09 kg/m² undergoing laparoscopic cholecystectomy due to gallbladder empyema. Patient had history of biliary sepsis, cardiomegaly, atelectasis of left lung apex, and chronic kidney disease. Severe inflammation of gallbladder necessitated higher pneumoperitoneum pressure up to 17 mmHg to facilitate visibility. The elevated intra-abdominal pressure combined with poor tissue turgor triggered extensive subcutaneous emphysema and massive hypercarbia, indicated by a surge in End-Tidal CO₂ (ETCO₂) reaching >70 mmHg, whereas arterial blood gas analysis revealed a PaCO₂ of 45 mmHg. This gradient anomaly occurred without an accompanying tachycardic response or oxygen desaturation. Temporary cessation of insufflation successfully stabilized the patient clinically. This case highlights the importance of vigilance regarding weak fascial turgor in underweight geriatric patients subjected to high intra-abdominal pressure, the impairment of CO₂ elimination due to atelectasis, and the crucial role of implementing multimodal analgesia with regional anesthesia techniques to prevent postoperative hypoventilation caused by opioid administration.